A STUDY ON THE VALIDITY OF VSTEP WRITING TESTS FOR THE SAKE OF REGIONAL AND INTERNATIONAL INTEGRATION - Quynh, Nguyen Thi Ngoc (VNU Journal of Foreign Studies; Vol 34 No 4, 2018)
In the context of rapid regional and international integration, particularly the official establishment of the ASEAN Economic Community in 2015, English capacity has become essential for Vietnamese people to create their competitiveness in employment, education and other opportunities. In the reform of English education and assessment in response to this demand, VSTEP tests were developed and introduced by the Ministry of Education and Training as national English assessment instruments. VSTEP tests are meant to be alternative to the existing expensive international standardised English tests (e.g. IELTS, TOEFL). But this requires VSTEP developers to take action to assure test validity. They also need to accumulate and disseminate evidence of validity of the tests to gain international recognition. By doing so, they have taken meaningful action to contribute to the nation’s international and regional integration. The paper highlights the commitment of ULIS-VNU as a VSTEP developing institution in this mission. It reports a recent VSTEP validation study as an example of this commitment.